Design and Development of Buck/Boost Converter for Maintaining the Constant DC Supply to Meet the Load Requirement. - Srikanth, M.; Poonam Upadhyay, Dr.; S. Tara Kalyani, Dr. (International Journal of Engineering and Technology, 2018)
As the conventional sources are coming to an extent, the new research era has been started with renewable energy sources like solar, wind etc. But with solar, wind power generation is not maintained constant due to the considering parameters like the variation in day-to-day temperature and irradiance. In order to overcome these variations and to meet the required rated power of the PV System, Maximum Power Point Tracking (MPPT) technique has been implemented. The present work describes the design and implementation of photo voltaic (PV) system with Buck/Boost converter. PV system output voltage always varied with irradiance and temperature, to control the voltage use DC-DC buck/boost converter. With the help of DC-DC converter and mode transition from buck to boost vice versa to maintain DC bus voltage constant and feeds to DC loads. Experimental results obtained from a 2.5KW system have verified the discussion and feasibility.Â Â